Rediscovering rural territories: Local perceptions and the benefits of collective mapping for sustainable development in Colombian communities - Juan Fernando Mendoza Ledezma (Research in Globalization, 2023)
Territorial analysis contributes to sustainable rural development practices and social action. Based on the qualitative methodological principle in the application of collective mapping, where peasants are the main actors in identifying local realities from a participatory geographic perspective, it is possible to characterize multiple rural realities and their community diversity. Firstly, recent qualitative methodological tools are identified to evaluate the scope of application and level of satisfaction of local actors in a Colombian rural context. Secondly, an explanation of the collective mapping method with communities is addressed for its subsequent application. Finally, local perspectives are examined based on the documentation of sociocultural and environmental components, threats, pollution, and places of interest within the territory that allow for the construction of the visual tool in active community participation workshops. Therefore, the article's purpose is to discuss the benefits of collective mapping as a playful and visual option for the rediscovery of the territory from local perspectives, leading to reflection on the need to create sustainable rural development strategies.
Keywords: 330; Collective mapping; Local perspectives; Qualitative methods; Rural communities; Sustainable development; Territory